Mayo Clinic guide to your baby's first year - Cook, Walter J.; Klaas, Kelsey M. (Mayo Clinic Press, 2020)
Mayo Clinic Guide to Your Baby<U+2019>s First Years is a trusted and essential resource for new and experienced parents alike. In this fully reviewed and updated second edition, you<U+2019>ll find practical guidance on caring for the new little one in your family, from birth to age 3. Inside you<U+2019>ll find evidence-based advice on giving your baby the best nutrition and introducing your toddler to solids, tips for forming healthy sleep habits, strategies for dealing with fussiness and tantrums, advice on establishing a secure bond with your child, monthly updates on your child<U+2019>s growth and development, and much more.